ARTI SIMBOLIS PAHATAN NAGA DI BAWAH CERAT YONI DARI SINGASARI - Rita Istari (Berkala Arkeologi, 2003)
Yoni, which is made of andesite stone, also has different meanings. The stones for yoni from the production process can be classified into four types, namely: very young stones (bala), young stones (Yuya), middle stones (Madnya) and old stones (wreddha). In addition, it can also be classified into: male stones, female stones and neutral stones. Stone color also has its own meaning, namely: white symbolizes equality, red symbolizes glory, yellow symbolizes prosperity and black symbolizes fertility. Stone for yoni is usually a type of female stone. This fact is in accordance with the opinion that says that yoni is a female element. Most of the yoni is made of black andesite stones, this is in line with the meaning of yoni as a female symbol associated with fertility.